The Effect of Annual Report Award Announcements on Stock Prices: Empirical Study of Annual Report Award Winning Companies Listed on the Indonesia Stock Exchange - Agustiningsih, Maulina; Saputra, Hafizul Rahmi (Golden Ratio of Data in Summary, 2025)
This study was conducted to test the effect of the Annual Report Award (ARA) on stock prices in companies that won the 2019 Annual Report Award listed on the Indonesia Stock Exchange. This study is an event study for 7 days, namely 3 days before, 1 day after, and 3 days after. The stock price used is the stock price at closing. The purpose sampling technique was used, and 12 companies that met the sample criteria were obtained. The hypothesis testing of this study used the data normality test, one-sample t-test, and paired sample t-test. The results of the hypothesis test showed that there was a difference in the average positive stock price before and during the announcement of the annual report award. There was no significant difference in the average positive stock price at the time and after the announcement and before and after the announcement of the annual report award. Thus, this study shows that the annual report award has an effect on stock prices before and during the announcement only.